Development of a multi-species SNP array for serrasalmid fish Colossoma macropomum and Piaractus mesopotamicus - Mastrochirico-Filho, Vito A. [UNESP]; Ariede, Raquel B. [UNESP]; Freitas, Milena V. [UNESP]; Borges, Carolina H. S. [UNESP]; Lira, Lieschen V. G. [UNESP]; Mendes, Natália J. [UNESP]; Agudelo, John F. G. [UNESP]; Cáceres, Pablo; Berrocal, Milthon H. M.; Sucerquia, Gustavo A. L.; Porto-Foresti, Fabio [UNESP]; Yáñez, José M.; et al. (Springer Nature, 2021)
Scarce genomic resources have limited the development of breeding programs for serrasalmid fish Colossoma macropomum (tambaqui) and Piaractus mesopotamicus (pacu), the key native freshwater fish species produced in South America. The main objectives of this study were to design a dense SNP array for this fish group and to validate its performance on farmed populations from several locations in South America. Using multiple approaches based on different populations of tambaqui and pacu, a final list of 29,575 and 29,612 putative SNPs was selected, respectively, to print an Axiom AFFYMETRIX (THERMOFISHER) SerraSNP array. After validation, 74.17% (n = 21,963) and 71.25% (n = 21,072) of SNPs were classified as polymorphic variants in pacu and tambaqui, respectively. Most of the SNPs segregated within each population ranging from 14,199 to 19,856 in pacu; and from 15,075 to 20,380 in tambaqui. Our results indicate high levels of genetic diversity and clustered samples according to their hatchery origin. The developed SerraSNP array represents a valuable genomic tool approaching in-depth genetic studies for these species.